Diagnostic Musculoskeletal Ultrasound for the Evaluation of the Lateral Elbow: Implications for Rehabilitation Providers - Robert C. Manske; Chris Wolfe; Phil Page; Michael Voight (International Journal of Sports Physical Therapy)
Musculoskeletal ultrasound (MSKUS) has emerged as a valuable diagnostic tool in the evaluation and management of lateral elbow pathologies. This imaging modality provides high-resolution, dynamic visualization of superficial soft tissue structures, making it particularly advantageous for assessing conditions such as lateral epicondylitis (tennis elbow), ligamentous injuries, radial tunnel syndrome, and other common disorders. This article reviews the utility of MSKUS for rehabilitation providers, focusing on its role in accurately identifying pathoanatomical changes, guiding treatment strategies, and monitoring therapeutic outcomes. Specific emphasis is placed on the integration of diagnostic ultrasound in clinical practice, imaging techniques, and its advantages compared to other modalities. By enhancing diagnostic accuracy and facilitating targeted interventions, MSKUS serves as a critical adjunct in the comprehensive care of lateral elbow conditions.